Caren condition reports - Guðmundur Ingi Jónsson 1996-; Filippus Darri Björgvinsson 1997-; Kristófer Gunnlaugsson 1995-; Hákon Ingi Einarsson 1995- (2020)
The Caren Condition Reports system was originally created by the team STACK: Shadow Legends as part of their final project at Reykjavik University in collaboration with Origo, Caren Condition Reports is a native application for managing the condition reports of rental cars. A common solution for managing the condition of rental vehicles, employed by car rentals in Iceland, is to fill out a condition report on paper when a vehicle goes out on rent and again when the vehicle is turned back in at the end of the rent. The condition report covers e.g. odometer, status, fuel status, any damages to the exterior or interior etc. If any damages on the car occur during the rental period, the customer must sign for them so that he’ll be registered responsible for the damages. This process is time consuming for both customers of a rental agency, as well as their employees. These condition reports are then stored by the rental agency in their physical form. The purpose of the Caren Condition Reports application is to digitize and streamline this process, with the goal of saving time for customers and rental employees, while also reducing paper consumption and storing valuable information about rental fleets in a database.